Composite electrode active material for inhibiting gas production of battery, preparation method of composite electrode active material and composite electrode

By copolymerizing phosphorus-containing monomers, etheroxy monomers and alkenyl imidazole salt compounds in situ on the surface of the electrode active material of the lithium-ion battery, forming the P-N functional copolymer-covered electrode active material, solving the problem of thermal runaway gas production in lithium-ion batteries and significantly improving the safety performance of the battery.

CN119812342AActive Publication Date: 2025-04-11INST OF CHEM CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510231813.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-11
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

Lithium-ion batteries produce a large amount of flammable gases during thermal runaway, resulting in fire and explosion risks. The prior art is difficult to effectively suppress this gas production phenomenon.

Method used

Phosphorus-containing monomers, etheroxy-containing monomers and alkenyl imidazole salt compounds are copolymerized in situ on the surface of the electrode active material by high-energy ball milling to form a P-N functional copolymer coated electrode active material to form a composite electrode active material.

Benefits of technology

When the battery is thermally out of control, the outer P-N functional copolymer releases free radicals to terminate the chain reaction, inhibits the formation of flammable gas, promotes the condensation of carbon, prevents fire and explosion, and significantly improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812342A_ABST
    Figure CN119812342A_ABST
Patent Text Reader

Abstract

The invention relates to a composite electrode active material for inhibiting gas production of a battery, a preparation method of the composite electrode active material and a composite electrode, the composite electrode active material is of a two-layer structure, the inner layer is an electrode active material, and the outer layer is a functional copolymer formed by in-situ polymerization; the functional copolymer is obtained by copolymerizing a phosphorus-containing monomer, an ether oxygen group-containing monomer and an alkenyl imidazole salt compound; and the outer layer accounts for 2-10 wt% of the composite electrode active material. The alkenyl imidazolium salt compound, the phosphorus-containing monomer and the ether oxygen group-containing monomer in a proper proportion are subjected to in-situ copolymerization on the surface of the electrode active material through a high-energy ball milling method to form the composite electrode active material, and the prepared composite electrode active material can effectively inhibit thermal runaway gas production of a battery while ensuring the electrochemical performance, so that the service life of the battery is prolonged. The safety performance of the battery is efficiently improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry and also to the field of energy material technology, and specifically relates to a composite electrode active material for inhibiting gas production in a battery, a preparation method thereof, and a composite electrode. Background Art

[0002] In recent years, with the rapid development of new energy electric vehicles, large-scale energy storage equipment and other fields, human demand for higher specific energy and safer energy storage devices is also growing rapidly. Alkali metal ion secondary batteries have become the focus of widespread attention, especially lithium ion batteries, which have been used in people's production and life due to their high energy density and long cycle stability. In recent years, with the continuous development of electrode materials for alkali metal ion secondary batteries, the energy density has been effectively improved, but the battery safety problem has become increasingly severe. High energy density batteries can cause serious safety accidents due to battery short circuits and thermal runaway behaviors caused by external impacts and high temperatures. Taking the common high-nickel ternary material as an example, lattice oxygen will be released during the thermal runaway of the battery, and violent exothermic reactions will occur with the electrolyte and the negative electrode material; in particular, the battery will also produce a large amount of flammable gas during the thermal runaway process, which is very likely to cause fire and explosion risks if it comes into contact with the outside.

[0003] At present, flame retardant additives and flame retardant electrolytes for lithium-ion batteries have received extensive attention from researchers, but there are few reports on the study of gas production during thermal runaway. During the thermal runaway process of the battery, the electrolyte will pyrolyze to produce a large amount of hydrocarbons (methane, ethane, ethylene) and a large amount of gas. After the positive electrode pyrolyzes and releases active oxygen, oxygen-poor combustion occurs. When the gas pressure is large enough, it breaks through the outside of the battery, causing a large amount of incompletely oxidized flammable mixed gas to enter the air, causing an external explosion that endangers life and property safety. Reducing the gas production during the thermal runaway process can prevent the gas pressure from being too high in the early stage of thermal runaway and thus breaking through the battery, delaying the explosion time, and at the same time reducing the power and risk of gas deflagration. Summary of the invention

[0004] In view of the above problems, the present invention proposes a composite electrode active material that inhibits gas production in batteries. The phosphorus-containing monomer, the ether-oxyl-containing monomer, and the vinyl imidazole salt compound are in situ copolymerized on the surface of the electrode active material by high-energy ball milling to form a PN functional copolymer-coated electrode active material, that is, a composite electrode active material with an inner layer of electrode active material and an outer layer of PN functional copolymer. During the thermal runaway process of the battery, the PN functional copolymer of the outer layer of the composite electrode active material can release free radicals in the early stage of thermal runaway, terminate the chain reaction, avoid the formation of a large amount of flammable gas, and promote the carbonization of the condensed phase, so as to inhibit the gas production during thermal runaway, prevent fire and explosion, and improve the safety of the battery. That is, the composite electrode active material of the present invention can effectively inhibit the gas production during thermal runaway of the battery while ensuring the electrochemical performance, and efficiently improve the safety performance of the battery.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A composite electrode active material for inhibiting battery gas production has a two-layer structure, wherein the inner layer is an electrode active material and the outer layer is a functional copolymer formed by in-situ polymerization; the functional copolymer is obtained by copolymerizing a phosphorus-containing monomer, an ether-oxyl-containing monomer, and an ethylene imidazole salt compound; the outer layer accounts for 2 to 10 wt% of the composite electrode active material.

[0007] Furthermore, the mass ratio of the phosphorus-containing monomer, the etheroxyl-containing monomer, and the alkenyl imidazole salt compound is 1:(0.2-0.8):(0.2-0.8), and preferably the mass ratio of the phosphorus-containing monomer, the etheroxyl-containing monomer, and the alkenyl imidazole salt compound is 1:(0.2-0.4):(0.4-0.6).

[0008] Preferably, the outer layer accounts for 4-6 wt % of the composite electrode active material.

[0009] Further, the vinyl imidazole salt compound is selected from at least one of 1-allyl-3-vinyl imidazole chloride, 1-allyl-3-vinyl imidazole bromide and 1-allyl-3-vinyl imidazole bis trifluoromethanesulfonyl imide, preferably 1-allyl-3-vinyl imidazole bis trifluoromethanesulfonyl imide. The vinyl imidazole salt compound is an ionic liquid monomer having an imidazole group. Through research, it is found that the vinyl imidazole salt compound is in situ copolymerized with a phosphorus-containing monomer and an ether-oxyl-containing monomer on the surface of an electrode active material to form a PN functional copolymer, that is, to form a composite electrode active material in which the PN functional copolymer is coated with the electrode active material. The composite electrode active material is used in a lithium-ion battery to significantly inhibit gas generation during thermal runaway of the battery. The possible reason is that alkenyl imidazole salt compounds are ionic liquids, in which the stability of ionic bonds is much higher than that of covalent bonds, so they have good high-temperature stability, which in turn improves the temperature resistance of the functional polymers obtained after copolymerization; on the other hand, the imidazole group contains nitrogen, which can synergize with phosphorus-containing compounds, decompose at high temperatures to produce phosphorus-containing compounds and nitrogen, neutralize free radicals, interrupt the combustion chain reaction, inhibit the production of combustible gases, and dilute flammable gases to reduce the risk of deflagration. In addition, alkenyl imidazole salt compounds can also enhance the ion transport effect of the electrode functional additive coating layer to ensure the capacity cycle stability of the battery. However, the proportion of each monomer needs to be controlled, and only when the proportion is appropriate can excellent inhibition of battery gas production and good electrochemical performance be obtained at the same time.

[0010] Further, the phosphorus-containing monomer is a phosphonate compound containing a carbon-carbon double bond or a phosphonic acid compound containing a carbon-carbon double bond, specifically selected from at least one of vinylphosphonic acid, dimethyl vinylphosphonate, diethyl vinylphosphonate, dimethyl allylphosphonate, diethyl allylphosphonate, dipropyl allylphosphonate, and diethyl isopropenylphosphonate; preferably dimethyl vinylphosphonate, diethyl vinylphosphonate, and diethyl allylphosphonate. In the early stage of thermal runaway temperature rise of the battery, the phosphonate can decompose to produce free radicals, participate in the combustion reaction and the electrolyte chain reaction, terminate the chain reaction through the three-body reaction, inertize the combustible substances such as the electrolyte and leave them in the carbon layer of the condensed phase, and play a role in inhibiting the gas production of thermal runaway. The decomposition product of the phosphonate is an important component for inhibiting the gas production. The phosphorus-containing monomer selected in the present invention has a small steric hindrance and is easy to introduce into the functional copolymer.

[0011] Furthermore, the etheroxy-containing monomer is an etheroxy-containing acrylate compound, specifically selected from at least one of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate and pentaerythritol tetraacrylate. The etheroxy-containing monomer selected in the present invention contains a large number of oxygen-containing substituents, which is conducive to the cleavage of carbon-carbon double bonds and polymerization, that is, copolymerization, and the flexible etheroxy group can play a toughening and strengthening role on the system. Among them, ethoxylated trimethylolpropane triacrylate also has a suitable number and length of branches, has a small steric hindrance, can further promote the occurrence of copolymerization and improve the crosslinking degree of the polymer.

[0012] Furthermore, the electrode active material is a positive electrode active material or a negative electrode active material, and the median particle size D50 is 5 to 12 μm; the positive electrode active material includes but is not limited to: one of sulfur carbon, lithium cobalt oxide, transition metal layered oxide, Prussian blue or phosphate material; the negative electrode active material includes but is not limited to: one of graphite, silicon carbon, hard carbon, and alloy material.

[0013] In a second aspect, the present invention also provides a method for preparing the composite electrode active material for inhibiting battery gas generation, comprising the following steps:

[0014] (S1) dissolving a phosphorus-containing monomer, an ether-oxy group-containing monomer, an ethylene imidazole salt compound and an initiator in a polar organic solvent to obtain a precursor solution, and then mixing the precursor solution with an electrode active material to obtain a precursor mixture;

[0015] (S2) placing the precursor mixture in a ball mill jar and subjecting it to in-situ copolymerization by high-energy ball milling, filtering and drying after the ball milling, to obtain a composite electrode active material having an inner layer of an electrode active material and an outer layer of a functional copolymer.

[0016] The precursor mixture obtained after mixing the precursor solution with the electrode active material is in a semi-wet state. Under the action of the initiator, the three monomers in the precursor solution copolymerize on the surface of the electrode active material during high-energy ball milling, thereby forming a functional copolymer coated on the surface of the electrode active material.

[0017] Furthermore, in step (S1), the total mass of the phosphorus-containing monomer, the ether-oxyl-containing monomer and the vinyl imidazole salt compound, the amount of the polar organic solvent, and the amount of the electrode active material are in a ratio of (2.5-15) g: (5-20) mL: 100 g, preferably (5-7.5) g: (5-20) mL: 100 g.

[0018] Furthermore, in step (S1), the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylimidazoline hydrochloride, dibenzoyl peroxide, and diisophenylpropene peroxide; and the amount thereof is 1 to 2 wt% of the total mass of the phosphorus-containing monomer, the ether-oxyl-containing monomer, and the vinyl imidazole salt compound. The amount of the initiator is more than that of the general preparation of high molecular weight linear polymers, so that there are more initiation sites, and a more branched and densely cross-linked functional copolymer can be formed.

[0019] Furthermore, in step (S1), the polar organic solvent is at least one of N,N-dimethylacetamide (DMAC) and N-methylpyrrolidone (NMP).

[0020] Furthermore, in step (S2), the conditions of the high-energy ball milling are: a rotation speed of 300 to 500 rpm, and a time of 3 to 8 hours; and the drying is performed at 70 to 90° C. for 6 to 12 hours.

[0021] In a third aspect, the present invention further provides a composite electrode, which is prepared by including the aforementioned composite electrode active material, a conductive agent, and a binder.

[0022] Beneficial effects of the present invention:

[0023] 1. In the present invention, phosphorus-containing monomers, ether-oxyl-containing monomers, and alkenyl imidazole salt compounds are in situ copolymerized on the surface of the electrode active material by high-energy ball milling to form a PN functional copolymer coated electrode active material, that is, a composite electrode active material. The decomposition temperature of the phosphonate group or phosphonic acid group in the functional copolymer is relatively low, and it can decompose and produce phosphorus-containing free radicals at the initial stage of thermal runaway temperature rise of the battery, participate in the combustion reaction and the electrolyte chain reaction, terminate the chain reaction through the three-body reaction, inertize the electrolyte and other combustible substances and leave them in the carbon layer of the condensed phase, play a role in inhibiting thermal runaway gas production, and prevent battery explosion and deflagration. The imidazole salt group in the functional copolymer has good thermal stability and will not decompose at low temperatures. After the battery reaches a high temperature, the nitrogen element will synergize with the phosphorus element to produce nitrogen on the one hand, which can dilute the flammable gas; on the other hand, it will promote the carbonization of the condensed phase, cover the larger electrolyte solvent molecules in the carbon layer, and avoid their decomposition and gas production. The synergistic effect of the phosphonate and imidazole salt groups realizes the control of the thermal runaway gas of the battery. The ether oxygen groups in the functional copolymer can promote copolymerization with phosphorus-containing monomers and alkenyl imidazole salt compounds, and improve the strength and toughness of the copolymer. The composite electrode active material prepared by the present invention through the reasonable proportion of alkenyl imidazole salt compounds and phosphorus-containing monomers and ether oxygen-containing monomers can significantly inhibit the gas production of battery thermal runaway, effectively improve the safety performance of the battery, and ensure good electrochemical performance.

[0024] 2. The preparation method of the composite electrode provided in the present invention is to introduce functional polymers on the surface of the electrode powder by in-situ copolymerization. Compared with the traditional blending and adding method, the composite electrode formed by in-situ copolymerization will not have an adverse effect on the cycle performance of the battery. The process of the present invention is convenient and efficient, and the electrode powder is directly modified without affecting the existing electrode preparation technology, which is suitable for large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the TEM image of the composite electrode active material prepared in Example 1.

[0026] Figure 2 This is a comparison chart of the gas production columns of the composite positive electrode made of the composite electrode active material of Example 1 and the composite positive electrode made of the composite electrode active material of Comparative Example 1 tested by EGA-MS at 50-700°C. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0028] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described can be obtained from commercial sources.

[0029] Example 1

[0030] (S1) isopropenylphosphonic acid diethyl ester, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride are mixed in a mass ratio of 1:0.2:0.2 to form a mixture of 2.5 g, and then the mixture and 0.04 g of azobisisobutyronitrile are dissolved in 10 mL of N,N-dimethylacetamide (DMAC) to obtain a precursor solution, and then the precursor solution is mixed with 100 g of a positive electrode active material NCM94 to obtain a precursor mixture;

[0031] (S2) placing the precursor mixture in a ball mill and ball milling it at 450 rpm for 5 h. After the ball milling, filtering and drying at 80° C. for 12 h, a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0032] The proportion of the outer layer functional copolymer in the entire composite electrode active material is calculated by the incremental method. It is calculated that in the prepared composite electrode active material, the outer layer functional copolymer accounts for 2.0wt% of the composite electrode active material.

[0033] TEM images of the prepared composite electrode active materials are shown in Figure 1 As shown. Figure 1 It can be seen that the composite electrode active material prepared in Example 1 has an obvious layered structure, the inner layer is the positive electrode active material NCM94, and the outer layer is the functional copolymer.

[0034] Example 2

[0035] The rest is the same as Example 1, except that: in step (S1), the mass ratio of diethyl isopropenylphosphonate, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride is 1:0.2:0.4; and finally a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0036] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.1wt% of the composite electrode active material.

[0037] Example 3

[0038] The rest is the same as Example 1, except that: in step (S1), the mass ratio of diethyl isopropenylphosphonate, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride is 1:0.4:0.4; and finally a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0039] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.1wt% of the composite electrode active material.

[0040] Example 4

[0041] The rest is the same as Example 1, except that: in step (S1), the mass ratio of diethyl isopropenylphosphonate, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride is 1:0.4:0.6; and finally a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0042] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.0 wt% of the composite electrode active material.

[0043] Example 5

[0044] The rest is the same as Example 1, except that: in step (S1), the mass ratio of diethyl isopropenylphosphonate, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride is 1:0.6:0.6; and finally a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0045] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.1wt% of the composite electrode active material.

[0046] Example 6

[0047] The rest is the same as Example 1, except that: in step (S1), the mass ratio of diethyl isopropenylphosphonate, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride is 1:0.8:0.6; and finally a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0048] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.1wt% of the composite electrode active material.

[0049] Example 7

[0050] The rest is the same as Example 1, except that: in step (S1), the mass ratio of diethyl isopropenylphosphonate, trimethylolpropane triacrylate, and 1-allyl-3-vinylimidazolium chloride is 1:0.8:0.8; and finally a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0051] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.2 wt% of the composite electrode active material.

[0052] Example 8

[0053] The rest is the same as Example 1, except that: in step (S1), diethyl vinylphosphonate is used instead of diethyl isopropenylphosphonate, and 1-allyl-3-vinylimidazole bistrifluoromethanesulfonyl imide salt is used instead of 1-allyl-3-vinylimidazole chloride; finally, a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0054] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 2.2 wt% of the composite electrode active material.

[0055] Example 9

[0056] The rest is the same as Example 2, except that: in step (S1), the total mass of the mixture formed by diethyl isopropenylphosphonate, trimethylolpropane triacrylate and 1-allyl-3-vinylimidazolium chloride is 5.0 g, and the amount of azobisisobutyronitrile is 0.06 g; finally, a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0057] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 4.3wt% of the composite electrode active material.

[0058] Example 10

[0059] The rest is the same as Example 2, except that: in step (S1), the total mass of the mixture formed by diethyl isopropenylphosphonate, trimethylolpropane triacrylate and 1-allyl-3-vinylimidazolium chloride is 7.5 g, and the amount of azobisisobutyronitrile is 0.9 g; finally, a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0060] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 6.4 wt% of the composite electrode active material.

[0061] Embodiment 11

[0062] The rest is the same as Example 2, except that: in step (S1), the total mass of the mixture formed by diethyl isopropenylphosphonate, trimethylolpropane triacrylate and 1-allyl-3-vinylimidazolium chloride is 11g, and the amount of azobisisobutyronitrile is 0.15g; finally, a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0063] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 8.4 wt% of the composite electrode active material.

[0064] Example 12

[0065] The rest is the same as Example 2, except that: in step (S1), the total mass of the mixture formed by diethyl isopropenylphosphonate, trimethylolpropane triacrylate and 1-allyl-3-vinylimidazolium chloride is 15g, and the amount of azobisisobutyronitrile is 0.18g; finally, a composite electrode active material with an inner layer of NCM94 and an outer layer of a functional copolymer is obtained.

[0066] By the incremental method, it was calculated that the outer layer functional copolymer accounts for 10.3wt% of the composite electrode active material.

[0067] Comparative Example 1

[0068] The rest is the same as Example 1, except that: in step (S1), 1-allyl-3-vinylimidazole chloride is not used, that is, diethyl isopropenylphosphonate and trimethylolpropane triacrylate are mixed in a mass ratio of 1:0.2 to form 2.5 g of a mixture.

[0069] Comparative Example 2

[0070] The rest is the same as Example 1, except that: in step (S1), diethyl isopropenylphosphonate is not used, that is, trimethylolpropane triacrylate and 1-allyl-3-vinylimidazolium chloride are mixed in a mass ratio of 0.2:0.2 (i.e., 1:1) to form a mixture of 2.5 g.

[0071] Testing and analysis

[0072] 1) Electrode gas generation behavior test: The composite electrode active materials prepared in each embodiment and comparative example were mixed with conductive carbon black Super P, polyvinylidene fluoride (PVDF) and organic solvent N-methylpyrrolidone (NMP) in a mass ratio of 8:1:1:20 to prepare a slurry; the slurry was then scraped on an aluminum foil with a scraping thickness of 300 μm, and dried in a blast oven at 70°C for 12 hours to obtain a composite electrode; finally, the composite electrode was used as the positive electrode, metallic lithium was used as the negative electrode, a polypropylene microporous membrane (Celgard2400) was used as a separator, and 1MLiPF6 electrolyte (the solvent was prepared in a volume ratio of ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1) was assembled into a half-cell. The specific method for testing the gas production behavior of the battery is as follows: the half-cell assembled as above is subjected to charge and discharge cycles on a blue-power battery tester, the charge and discharge rate is 0.2C (1C=230mAh / g), and the charge and discharge voltage range is 2.5-4.35V; after 5 cycles, the battery is charged to 4.4V and charged at a constant voltage until the current is less than 0.05C, then the battery is disassembled and the fully charged composite electrode sheet is taken out; after the composite electrode sheet is cleaned with dimethyl carbonate, the coating on the surface is scraped off and weighed, and the electrode is added into a crucible together with the electrolyte (volume-to-mass ratio is 1μL / mg), and an evolved gas analysis-mass spectrometry (EGA-MS) test is performed, the heating rate is 10℃ / min, and the test temperature is 50-700℃.

[0073] The intensity of the test peak reflects the amount of gas released by the sample at the test temperature. The higher the peak intensity, the more gas is released. The gas column comparison of the composite positive electrode made of the composite electrode active material of Example 1 and the composite positive electrode made of the composite electrode active material of Comparative Example 1 at 50-700°C by EGA-MS is shown in FIG. Figure 2 shown; from Figure 2 It can be clearly seen that the gas production of the composite positive electrode made of the composite electrode active material of Example 1 is significantly lower than that of Comparative Example 1. The specific gas production test results of the composite positive electrodes made of the composite electrode active materials of each embodiment and comparative example are shown in Table 1.

[0074] 2) Electrochemical performance test: The half-cells assembled in the above embodiments and comparative examples were subjected to electrochemical performance test on a blue battery tester. After 0.1C charge and discharge for 3 times, they were cycled at a rate of 0.33C with a charge and discharge voltage range of 2.5 to 4.35V. The initial coulombic efficiency and the capacity retention rate after 100 cycles were tested. The test results are shown in Table 1.

[0075] Table 1 Performance test

[0076]

[0077] It can be seen from Table 1 that the composite electrode active material prepared in the embodiment of the present invention has obvious performance in inhibiting battery gas production. The total gas production intensity of the composite electrode active material prepared in the embodiment in the EGA-MS test is only 40-50% of that of the comparative example, indicating that the total gas production of the composite electrode active material prepared in the embodiment within the range of 50-700°C is 40-50% of that of the comparative example, and the gas production intensity of flammable methane, ethane and propane is also significantly lower than that of the comparative example.

[0078] From the comparison between Examples 1-7 and Comparative Examples 1-2, it can be seen that the functional copolymer produced by copolymerization of three monomers (phosphorus-containing monomer, ether-oxyl-containing monomer and vinyl imidazole salt compound) has good performance in inhibiting battery gas production when coating the electrode active material to form a composite active material.

[0079] From the comparison between Example 1 and Examples 8-12, it can be seen that as the proportion of the functional copolymer in the outer layer increases, the performance of the composite electrode active material in inhibiting battery gas production gradually improves. However, when the proportion of the functional copolymer in the outer layer increases to 6% of the composite electrode active material, its performance in inhibiting gas production is basically no longer improved.

[0080] It can be seen from the electrochemical performance test data in Table 1 that the composite electrode active material prepared in the embodiment of the present invention has a significant inhibitory effect on battery gas production, does not reduce the initial coulombic efficiency, and can improve the cycle performance of the battery.

[0081] In summary, the composite electrode active material of the present invention significantly suppresses the gas production caused by thermal runaway of the battery while ensuring good electrochemical performance.

Claims

1. A composite electrode active material for inhibiting battery gas production, which has a two-layer structure, the inner layer is an electrode active material, and the outer layer is a functional copolymer formed by in-situ polymerization; characterized in that: The functional copolymer is obtained by copolymerizing a phosphorus-containing monomer, an ether-oxyl-containing monomer, and an ethylene imidazole salt compound; and the outer layer accounts for 2-10 wt% of the composite electrode active material.

2. The composite electrode active material according to claim 1, characterized in that The mass ratio of the phosphorus-containing monomer, the ether-oxyl-containing monomer, and the alkenyl imidazole salt compound is 1:(0.2-0.8):(0.2-0.8), and preferably the mass ratio of the phosphorus-containing monomer, the ether-oxyl-containing monomer, and the alkenyl imidazole salt compound is 1:(0.2-0.4):(0.4-0.6).

3. The composite electrode active material according to claim 1, characterized in that: The outer layer accounts for 4-6 wt % of the composite electrode active material.

4. The composite electrode active material according to claim 1, characterized in that: The vinyl imidazole salt compound is selected from at least one of 1-allyl-3-vinylimidazole chloride, 1-allyl-3-vinylimidazole bromide and 1-allyl-3-vinylimidazole bis(trifluoromethanesulfonyl)imide, preferably 1-allyl-3-vinylimidazole bis(trifluoromethanesulfonyl)imide.

5. The composite electrode active material according to claim 1, characterized in that: The phosphorus-containing monomer is a phosphonate compound containing a carbon-carbon double bond or a phosphonic acid compound containing a carbon-carbon double bond, specifically at least one selected from vinylphosphonic acid, dimethyl vinylphosphonate, diethyl vinylphosphonate, dimethyl allylphosphonate, diethyl allylphosphonate, dipropyl allylphosphonate, diethyl isopropenylphosphonate, preferably dimethyl vinylphosphonate, diethyl vinylphosphonate, diethyl allylphosphonate; and / or The etheroxy group-containing monomer is an etheroxy group-containing acrylate compound, specifically at least one selected from ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate and pentaerythritol tetraacrylate.

6. The composite electrode active material according to claim 1, characterized in that: The electrode active material is a positive electrode active material or a negative electrode active material, and the median particle size D50 is 5 to 12 μm.

7. The method for preparing a composite electrode active material for inhibiting battery gas generation according to any one of claims 1 to 6, characterized in that: The following steps are involved: (S1) dissolving a phosphorus-containing monomer, an ether-oxy group-containing monomer, an ethylene imidazole salt compound and an initiator in a polar organic solvent to obtain a precursor solution, and then mixing the precursor solution with an electrode active material to obtain a precursor mixture; (S2) placing the precursor mixture in a ball mill jar and subjecting it to in-situ copolymerization by high-energy ball milling, filtering and drying after the ball milling, to obtain a composite electrode active material having an inner layer of an electrode active material and an outer layer of a functional copolymer.

8. The preparation method according to claim 7, characterized in that: In step (S1), the total mass of the phosphorus-containing monomer, the ether-oxyl-containing monomer and the vinyl imidazole salt compound, the amount of the polar organic solvent, and the amount of the electrode active material are in the ratio of (2.5-15) g: (5-20) mL: 100 g, preferably (5-7.5) g: (5-20) mL: 100 g.

9. The preparation method according to claim 7, characterized in that: In step (S1), the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylimidazoline hydrochloride, dibenzoyl peroxide, and diisophenylpropene peroxide; and the amount thereof is 1 to 2 wt% of the total mass of the phosphorus-containing monomer, the ether-oxyl-containing monomer, and the vinyl imidazole salt compound; and / or In step (S1), the polar organic solvent is at least one of N,N-dimethylacetamide and N-methylpyrrolidone; and / or In step (S2), the conditions of the high-energy ball milling are: a rotation speed of 300-500 rpm, and a time of 3-8 hours; and the drying is performed at 70-90° C. for 6-12 hours.

10. A composite electrode, characterized in that: The composite electrode is prepared from the above-mentioned composite electrode active material, a conductive agent and a binder.

Citation Information

Patent Citations

  • Phosphorus-containing polymer hydrogel as well as preparation method and application thereof

    CN113694903A

  • Positive electrode slurry, composite positive plate and lithium ion battery

    CN116632243A

  • Composite electrode slurry for inhibiting thermal runaway of battery, composite electrode and preparation method of composite electrode slurry

    CN118315590A

  • Low-temperature polymerized gel electrolyte and battery comprising same

    WO2024217121A1